1997
DOI: 10.1074/jbc.272.39.24673
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Functional Interactions between the α2A-Adrenoreceptor and Acylation-resistant Forms of Gi1α by Expressing the Proteins from Chimeric Open Reading Frames

Abstract: Co-expression of the ␣ 2A -adrenoreceptor with a pertussis toxin-resistant (C351G), but not with an also palmitoylation-resistant (C3S/C351G), form of the ␣ subunit of G i1 resulted in agonist-induced, pertussis toxinindependent, GTP hydrolysis. Construction and expression of a chimeric fusion protein between the receptor and C351G G i1 ␣ generated a membrane protein in which the G protein element was activated by receptor agonist. An equivalent fusion protein containing C3S/C351G G i1 ␣ rescued the ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 34 publications
0
61
1
Order By: Relevance
“…Although there is no formal proof that this amino acid becomes palmitoylated in the fusion proteins used herein the equivalent Cys residue does become palmitoylated, and can be regulated in an agonist-dependent manner, in a ␤ 2 -adrenoreceptor-G␣ s fusion protein (51). This does not appear directly relevant for the the present studies, however, as it has previously been shown that an ␣ 2A -adrenoreceptor-G␣ i1 fusion protein in which this Cys is substituted by Ala allows as effective agonist stimulation of the G protein GTPase activity as in a wild type fusion protein (19). There has been considerable recent interest in observations that a range of RGS family members including RGS4, RGS10 (52), and RGS16 (53) can be palmitoylated.…”
Section: Construct Gtp K M (Nm)mentioning
confidence: 65%
See 1 more Smart Citation
“…Although there is no formal proof that this amino acid becomes palmitoylated in the fusion proteins used herein the equivalent Cys residue does become palmitoylated, and can be regulated in an agonist-dependent manner, in a ␤ 2 -adrenoreceptor-G␣ s fusion protein (51). This does not appear directly relevant for the the present studies, however, as it has previously been shown that an ␣ 2A -adrenoreceptor-G␣ i1 fusion protein in which this Cys is substituted by Ala allows as effective agonist stimulation of the G protein GTPase activity as in a wild type fusion protein (19). There has been considerable recent interest in observations that a range of RGS family members including RGS4, RGS10 (52), and RGS16 (53) can be palmitoylated.…”
Section: Construct Gtp K M (Nm)mentioning
confidence: 65%
“…In the case of the ␣ 2A -adrenoreceptor, acylation occurs at Cys 442 (49). However, mutation of this residue to Ala does not intefere with the effectiveness of coupling of this receptor either in co-expression studies (49) or following construction of this mutant into an ␣ 2A -adrenoreceptor-G i1 ␣ fusion protein (19). G␣ i1 is palmitoylated at Cys 3 (50) as are the other G i family ␣ subunits.…”
Section: Construct Gtp K M (Nm)mentioning
confidence: 99%
“…These have included linking the G protein to a single transmembrane-spanning element of a GPCR (50). However, the current approach ensures proximity of the G protein to the GPCR and has been successfully applied previously for acylation-resistant forms of G␣ i1 (51).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GFP is not the only protein that can be attached to the COOH-terminal tail of a G protein-coupled receptor without disrupting function. We and others have produced fusion proteins in which the ␣ subunits of heterotrimeric G proteins have been attached directly to the COOH-terminal tail of various receptors (42)(43)(44)(45)(46). From the long isoform of the rat TRH receptor, we generated for these studies both an NH 2 -terminally epitope-tagged form of the receptor (VSV-TRHR) and subsequently the final chimeric protein (VSV-TRHR-GFP).…”
Section: Discussionmentioning
confidence: 99%